Fish oil supplementation in rheumatoid arthritis - P. Spinella; F. Oliviero; C. Sales (PAGEPress Publications, 2011)
The beneficial properties of fish oil are well known and are related to its fatty acid composition rich in omega-3 polyunsaturated fatty acids. In the last years a variety of epidemiological and clinical studies have demonstrated the efficacy of fish oil supplementation in the rheumatic diseases, in particular in rheumatoid arthritis. The anti-inflammatory effects of fish oil are linked to the production of alternative eicosanoids, to the reduction of proinflammatory cytokines, to the inhibition of the activation of T lymphocytes and of catabolic enzymes. Fish oil supplementation could represent a valuable support to the traditional pharmacological treatment of rheumatoid arthritis.